Intracoronal esthetic restorative materials in pediatric dentistry: concepts revisited - Mehta, Vivek; Srivastava, Nikhil (International Journal Of Community Medicine And Public Health, 2024)
A plethora of restorative materials currently exist to repair carious teeth in children, and numerous options are available for restoring primary and young permanent incisors and molars esthetically. Intracoronal esthetic restorations most commonly used for primary and young permanent dentition include direct restorative materials mainly as composite resins, glass ionomer cement, their modifications, and indirect restorative materials like laboratory-processed inlays, onlays, overlays, and endo-crown prostheses. A pediatric dentist needs to be aware of the composition, indications, advantages, and limitations associated with these restorative materials to employ them judiciously in children. However, the clinical data is insufficient to suggest the most superior type of restoration to be used in pediatric patients. Through this platform; the authors discuss esthetic restorative treatment alternatives along with established recommendations and directions for future developments, familiarizing clinicians with evidence for and against the use of appropriate materials for pediatric restorative dentistry.